1999
DOI: 10.1080/j.1600-0412.1999.780903.x
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis in pregnancy, Diagnosis, management and complications

Abstract: Appendicitis in pregnancy should be suspected when a pregnant woman complains of new abdominal pain. No laboratory finding was found to be diagnostic for acute appendicitis during pregnancy. Considerable fetal loss was found after appendectomy during pregnancy in the first and second trimester. No increase in pregnancy complications in cases with perforated appendicitis was observed. The combination of symptoms and clinical judgement is still vital in deciding which patient needs surgical treatment. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
93
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 0 publications
10
93
2
5
Order By: Relevance
“…According to one review, histologically proven appendicitis was found in 22% of previously healthy nonpregnant patients with pneumococcal peritonitis [7]. Signs and symptoms of appendicitis can be suppressed during pregnancy, and local inflammatory changes might be less prominent [8], causing a delay in diagnosis and treatment.…”
Section: To the Editorsmentioning
confidence: 97%
“…According to one review, histologically proven appendicitis was found in 22% of previously healthy nonpregnant patients with pneumococcal peritonitis [7]. Signs and symptoms of appendicitis can be suppressed during pregnancy, and local inflammatory changes might be less prominent [8], causing a delay in diagnosis and treatment.…”
Section: To the Editorsmentioning
confidence: 97%
“…Acute appendicitis is the most common surgical emergency in pregnancy and is associated with fetal loss and maternal death 1314. A fetal loss rate of 8% was reported in a Turkish study of 52 women with acute appendicitis who underwent surgery 15.…”
Section: What Is the Next Investigation?mentioning
confidence: 99%
“…
Appendicitis in pregnancy 277because the rate of fetal loss and early delivery in women with perforated appendicitis is substantially higher then cases of simple appendicitis [6][7][8]11,18 .Curiously, the risk of acute appendicitis is lower in the pregnant than the nonpregnant female population, with the majority of cases in pregnancy occurring in the second trimester 4,9,13,19 . Andersson et al 19 found there to be an inverse relationship between pregnancy and appendicitis.
…”
mentioning
confidence: 99%
“…
Appendicitis in pregnancy 277

because the rate of fetal loss and early delivery in women with perforated appendicitis is substantially higher then cases of simple appendicitis [6][7][8]11,18 .

Curiously, the risk of acute appendicitis is lower in the pregnant than the nonpregnant female population, with the majority of cases in pregnancy occurring in the second trimester 4,9,13,19 . These include: feelings of malaise, nausea/vomiting, constipation/bowel irregularity, urinary frequency, abdominal and pelvic discomfort and leukocytosis 4,7,[9][10][11] .The most common clinical presentation is vague pain in the lower right quadrant with rebound tenderness 4,6,12,13,18,21 . Furthermore, they postulated that this relationship may be linked to the hypothesis of Wegmann et al 20 who thought that the immune system favours humoral immunity mediated by TH2 cells during pregnancy.

…”
mentioning
confidence: 99%
See 1 more Smart Citation